SPECIFIC FEATURES OF THE DEVELOPMENT OF CHRONIC KIDNEY DISEASE IN ADOLESCENTS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Chronic kidney disease (CKD)-considered one of the global medical, economic and social pressing problems that can negatively affect the health of the population and the economic condition of the country, occurs in almost 15% of the population of developed countries, and the resulting CKD is characterized by a high incidence of disability and death among patients.